Sharia-Based Financial Practices in Culinary MSMEs: Sustainability and Ethical Perspectives - Kusumawati, Sri Dewi (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze sharia-based financial practices in culinary MSMEs by reviewing the perspective of sustainability and business ethics. The background of this research is based on the increasing role of culinary MSMEs in the national economy and the need for a financial system in accordance with sharia principles. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observations, and documentation on culinary MSME actors who apply sharia finance principles. The results of the study show that sharia-based financial practices are able to support business sustainability, especially in economic and social aspects, such as cash flow management, fair wages, and social involvement. However, the environmental dimension still faces obstacles, especially in waste management and the use of environmentally friendly packaging. In terms of ethics, sharia principles such as honesty, transparency, and compliance with halal have strengthened consumer trust and business image. Challenges faced include low Islamic financial literacy and limited access to formal Islamic financing. This research emphasizes the importance of integrating Islamic finance with sustainability practices and business ethics to strengthen the competitiveness of culinary MSMEs. Therefore, efforts are needed to increase Islamic financial literacy and develop more inclusive access to Islamic financing so that the sustainability of MSMEs can be achieved comprehensively